CONSUMERS, PRODUCERS AND THE EFFICIENCY OF MARKETS - Abrorjon Habibullayev Ahmadali ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Having described the way markets allocate scarce resources we now need to address the question of whether these market allocations are desirable. In other words, our analysis has been positive (what is) rather than normative (what should be). We know that the price of a good adjusts to ensure that the quantity of a good supplied equals the quantity demanded. But, at this equilibrium, is the quantity of the good produced and consumed too small, too large or just right? In this article we take up the topic of welfare economics, the study of how the allocation of resources affects economic well-being.